Analisis Kinerja Keuangan PT Bank Mega Syariah dengan RGEC, Efisiensi, Stabilitas, dan Financial Distress Periode 2019-2023 - Husna, Nizzatul; Fadhilah, Najwa Nurfan; Eliza, Nurul (Jurnal Ilmiah Wahana Akuntansi, 2024)
This study evaluates the health of PT Bank Mega Syariah from 2019 to 2023 using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital). The analysis includes operational efficiency, financial stability, and bankruptcy risk with annual financial report data. The results show that the RGEC method is effective in measuring the health of Islamic banks, with fluctuations in profitability and risk management. Despite efficiency challenges, the G-score model indicates low bankruptcy risk. This study provides strategic recommendations to improve financial and operational performance, relevant to regulators and stakeholders in the development of Islamic banking in Indonesia.